Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.12968/denu.2017.44.10.979
|View full text |Cite
|
Sign up to set email alerts
|

Errors and adverse events in dentistry – a review

Abstract: As dental professionals we must change the way we think about error. By adopting a more positive, constructive approach, centred around analysing why errors happen, we can then accept our vulnerability and design systems and protocols to prevent errors from occurring. Errors are inextricably linked to human behaviour. Human factors in healthcare are concerned with ensuring patient safety through promoting efficiency, safety and effectiveness by improving the design of technologies, processes and work systems. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…A move towards a more just culture of analysing systems rather than placing blame on the practitioner is vital to effecting positive change. 7 Failing to report errors and share learning have previously been identified as weaknesses in dental schools when compared to hospitals. 8 However, our survey highlights many dental schools have shown a proactive approach to patient safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A move towards a more just culture of analysing systems rather than placing blame on the practitioner is vital to effecting positive change. 7 Failing to report errors and share learning have previously been identified as weaknesses in dental schools when compared to hospitals. 8 However, our survey highlights many dental schools have shown a proactive approach to patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…6 Strategies to foster strong patient safety cultures have been advised as a way to minimise errors in health care. 7 In the United States, researchers noted a more positive patient safety culture within dental schools when compared to medical hospitals, although weaknesses in reporting events and organisational learning were identified in the school setting. 8 A recent study of a UK dental school identified that students had a good understanding and positive attitude towards patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…In-house competency frameworks for safety training can be advantageous, In the absence of readily-available, tailored, primary care team training in human factors (HF), responsibility falls on individual primary care practice owners to teach the basics of HF to the team. 9 Teaching human fallibility and the importance of a blame-free ethos is paramount in establishing a positive, sustained, patient safety culture. Simulations of clinical scenarios based around HF within the primary care environment in which staff work, can be simple, yet fulfilling training exercises on human, social and cognitive factors.…”
Section: Teaching and Trainingmentioning
confidence: 99%
“…6 Most medical errors are now attributed to HF rather than deficiencies in knowledge or technical ability. 7 The National Quality Board has created a concordat among healthcare organisations including NHS England, the Care Quality Commission, and Health Education England to take action and embed the principles of HF within our health service. 8 The National Advisory Board for Human Factors in Dentistry, established in 2018, recently published its position paper and aims to “raise awareness and understanding of the interplay of the multitude of factors called Human Factors that affect the provision of high-quality dental care leading to unforeseen outcomes compromising patient and team safety.” 9 They provide guidance on the steps dental teams can take to increase awareness of HF on patient and team safety, as well as clear definitions of patient safety terminology.…”
Section: Human Factors and Non-technical Skillsmentioning
confidence: 99%